Transitions between dynamically simulated motions: Leaping, tumbling, landing and balancing - Wooten, W. L.; Hodgins, J. K. (Proceedings of ACM SIGGRAPH '97. August 3-8, 1997, Los Angeles, California, 1997)
sis control systems and transitions between them by generating a diverse set of behaviors for a male and female character, including an inward 2-1/2 somersault pike, standing forward and backward somersaults, a handspring, and variFrom the Visual Proceedings of ACM SIGGRAPH '97, Held August 3--8, 1997, in Los Angeles, California. ous leaping maneuvers. We have developed a small set of basis controllers to demonstrate the feasibility of this approach. The balance controller prevents the character from falling down by keeping the ground projection of the character 's center of mass within the area of support. Two parameters modify the behavior of the balance controller---the height of the hips above the ground and an offset for the desired location of the projected center of mass. The leaping controller propels the character into the air. The height of the leap can be controlled by modifying the height of the hips at the beginning of the leap. Horizontal dis